A Comparative Study of Homogeneous and Heterogeneous Photo-fenton Process for Textile Wastewater Treatment. (2016) - Sreeja, P.H.; Sosamony, K.J.
Abstract: In this study, the COD removal and Dye removal efficiencies of homogeneous and heterogeneous photo-Fenton process are compared for the treatment of synthetic textile wastewater. The effect of parameters like pH, catalyst dosage, H2 O2 dosage and U V power are evaluated using Taguchi's experimental design. In heterogeneous photo-Fenton process copper modified iron oxide is used as the catalyst. The heterogeneous process showed the highest removal efficiencies under optimum condition with COD removal of 62% and Dye removal of 85%.For homogeneous photo-Fenton process COD removal and Dye removal are 47% and 82% respectively.